Caracterização clínica, epidemiológica, neurorradiológica e genética de pacientes com síndrome Fosmn - Pinto, Wladimir Bocca Vieira de Rezende [UNIFESP] (2018)
Objectives: Perform clinical characterization of motor and nonmotor aspects of FOSMN (facialonset sensory and motor neuronopathy) syndrome in Brazilian patients. Secondary objectives included: (i) evaluation of the genetic basis associated with FOSMN syndrome, especially in patients with familial history of MND (Motor Neuron Disease)/ALS (Amyotrophic Lateral Sclerosis) or other neurodegenerative diseases or a specific genetic spectrum; (ii) discussion of the main pathophysiological mechanisms involved with FOSMN syndrome correlating genetic findings observed in sporadic and familial MND/ALS and the main atypical variants. Methods: A retrospective clinical study was performed and a wide evaluation and review of clinical, laboratorial, neurophysiological and neurogenetic findings from ten nonrelated Brazilian patients with FOSMN syndrome selected from a group of 900 patients followedup from January 2012 and December 2016 in MND/ALS Unit, Division of Neuromuscular Diseases, Federal University of São Paulo (UNIFESP), São Paulo, Brazil. Medical records were verified including clinical characterization of signs and symptoms of motor and nonmotor compromise (including basic cognitive profile), laboratorial evaluation, neuroimaging studies and specific genetic exams. Genetic studies were reviewed and performed in cases with previously established or suggestive familial (or hereditary) context of a specific neurodegenerative phenotype of familial MND/ALS. Results: Mean age at onset of symptoms was at 52.1 years, with equal involvement of men and women. Patients presented with hemifacial paraesthesia (including oral cavity mucosa) or bialteral paraesthesia and weakness in the face, evolving with dysphagia, dysphonia and amyotrophy in the face and tongue, eventually with compromise of other bulbar and pontine cranial nerves, and finally at latestages with dropped head syndrome, weakness in the upper limbs and sensory changes in the upper limbs in a similar pattern to syryngomyelialike. Eight patients presented with multidomain cognitive compromise, half of them with cortical brain atrophy and none of them with spontaneous cognitive or behavioral complaints. All patients had diffuse chronic denervation involving the bulbar, cervical and thoracic myotomes (most of them also with acute denervation) and abnormal testing of the blink reflex. Positive family history of neurodegeneration was identified in six cases, disclosing monogenic pathogenic variants in three families (VCP, TARDBP and CHCHD10 genes). The worst clinical prognosis regarding mortality and severe motor handicap was observed in one single case with early bulbaronset of symptoms and high tendency of early cervical weakness (droppedhead syndrome). Conclusion: This case series has demonstrated new clinical and neurogenetic findings associated with FOSMN syndrome: (i) motor clinical course is not always benign with worse prognosis associated with “droppedhead” syndrome and early bulbar compromise; (ii) although considered a sporadic MND in current literature, FOSMN syndrome may be part of a complex familial neurodegenerative spectrum; (iii) it has been observed the association of FOSMN syndrome in three patients with pathogenic variants in TARDBP, VCP and CHCHD10 genes; (iv) cognitive compromise may be underdiagnosed in cases of FOSMN syndrome possibly due to subclinical involvement.